Analysis of Urban Development Suitability - Chakma, S. (Springer, 2013)
This chapter applies multi-criteria evaluation (MCE) within a GIS to the problem of land suitability assessment in Dhaka. A total of eight factors extracted from a spatial database were used as predictors with the analytic hierarchy process (AHP) followed by weighted linear combination (WLC) being used to identify areas appropriate for future urban development. The results revealed that approximately 21 % of land of the study area is highly suitable for urban development, whereas 29 % of land is moderately suitable. About 26 % of land, comprised of existing urban areas and waterbodies, is shown to be either unsuitable or of very low suitability for urban development although some redevelopment or vertical expansion may be possible. The analysis shows that GIS-based urban development suitability has major implications for a rapidly growing city such as Dhaka which can help urban planners and decision-makers to make better land-use planning decisions.